The mechanistic basis of metabolic response to surgery and postoperative insulin resistance in patients having abdominal surgery - Varadhan, Krishna Kumar (2015)
Postoperative insulin resistance (POIR) is a hallmark feature in patients having major abdominal surgery. Surgical stress may induce changes in metabolic pathways that perturb glucose homeostasis, resulting in stress hyperglycaemia. The studies described in the present thesis set out to examine the evidence behind (1) the ‘Enhanced Recovery After Surgery’ pathway (2) preoperative carbohydrate drinks (CHO), in attenuating the surgical stress response and (3) to investigate the mechanistic basis of metabolic response to surgery and the development of postoperative insulin resistance in patients having major abdominal surgery.